Chaotic convection of viscoelastic fluid in porous medium under G-Jitter - Bhadauria, Beer Singh; Singh, A.; Singh, M.K. (Zielona Góra: Uniwersytet Zielonogórski)
The present article aims at investigating the effect of gravity modulation on chaotic convection of a viscoelastic fluid in porous media. For this, the problem is reduced into Lorenz system (non-autonomous) by employing the truncated Galerkin expansion method. The system shows transitions from periodic to chaotic behavior on increasing the scaled Rayleigh number R.
Keywords: non-linear theory; gravity modulation; chaotic convection